Relay participated–new-type building energy management system: An energy-efficient routing scheme for wireless sensor network–based building energy management systems - Kewang Zhang; Qizhao Wu; Xin Li (International Journal of Distributed Sensor Networks)
With the development of wireless sensor networks, many building energy management systems are getting to adopt wireless sensor network as their communication infrastructure. However, the existing wireless sensor network protocols cannot satisfy the energy-saving demand of building energy management systems. Considering the characteristics of the building energy management system wireless sensor networks, a novel energy-efficient routing scheme is proposed called relay participated–new-type building energy management system. Nodes in the building energy management system wireless sensor networks are divided into two types: energy-limited nodes (battery powered) and energy-unlimited nodes (main powered, solar charger, or heat energy powered). Relay participated–new-type building energy management system allows energy-unlimited nodes to temporarily receive packets that are routed to a nearby energy-limited nodes. In this way, time synchronization for low-power sleep at media access control layer is no longer required, which reduces the delay and control overhead at media access control layer dramatically. Relay participated–new-type building energy management system reduces energy usage of energy-limited nodes and extend the lifetime of wireless sensor networks in new-type building energy management systems. Simulation results show that the relay participated–new-type building energy management system protocol significantly improves energy efficiency of limited energy nodes and reduces latency as compared to ad hoc on-demand distance vector–sensor medium access control and low-energy adaptive clustering hierarchy.